VARIABILITY STUDIES IN AFRICAN MARIGOLD (TAGETES ERECTA L.) - A. K. VISHNUPRIY; M. JAWAHARLAL; N. MANIVANNAN (The Bioscan, 2015)
The present investigation was undertaken to study the genetic parameters such as, heritability, genotypic and phenotypic coefficient of variation (GCV, PCV) for ten characters of F2 progenies in two cross combinations viz., Coimbatore Local Orange X Siracole and Siracole X Coimbatore Local Orange. Both crosses differed in mean performance for all the characters except for number of flowers per plant and number of days taken for flower bud appearance. Phenotypic coefficient of variation was higher than the genotypic coefficient of variation. High PCV and GCV were observed for number of primary branches, number of secondary branches, single flower weight, flower compactness and total flower weight. High heritability was observed for days taken for flower bud appearance, total crop duration and number of flowers per plant. High heritability along with high genetic advance as percent mean were recorded in both the crosses for days taken for flower bud appearance and number of flowers per plant whereas moderate to high heritability and genetic advance as percent mean for other characters in both crosses. As the high heritability and genetic advance as percent mean are due to additive type of gene action selection will be effective for all the characters in both crosses.